The concept of Brazilian Jurisdictional Waters and the protection of international marine spaces by the coastal state - Zelesco Barretto, Rafael (Revista de Derecho Público, 2024)
Brazil uses the concept of Brazilian Jurisdictional Waters (BJW) in its national legislation to refer to the maritime spaces over which the country exercises some degree of jurisdiction. This paper investigates its compatibility with the law of the sea, as BJW also encompass the waters above Brazil’s extended continental shelf, and are criticized as an appropriation of the high seas. The study takes into account the need to protect the interests of the coastal state on its continental shelf, and concludes that the extension of the BJW is compatible with the law of the sea.